Poder de control empresarial mediante detectives privados y validez de sus pruebas - Poquet Catalá, Raquel (Revista General del Derecho del Trabajo y de la Seguridad Social, 2021)
In this work, it is carried out an analysis of the value of the reports made by private detectives in the workplace, both from the point of view of respecting the limits in the action carried out by the private detective to obtain the information, and from the procedural point of view, as a means of evidence. For this reason, firstly, it is realized a study of the figure of the private detective, from the regulatory point of view, and then it is studied the power of surveillance and control, especially through private detectives, and its possible conflict with the right to a intimacy of workers. Finally, it is analyzed the probative value of the detective's reports in the social process.
Power of business control through private detectives and the validity of their evidence
Keywords: private detective; report; witness evidence; intimacy; surveillance; Emerging